Eradication of methicillin resistant Staphylococcus aureus detected for the first time in cystic fibrosis: A single center observational study. Issue 10 (5th July 2016) - Kappler, Matthias; Nagel, Felicitas; Feilcke, Maria; Kröner, Carolin; Pawlita, Ingo; Naehrig, Susanne; Ripper, Jan; Hengst, Meike; von Both, Ulrich; Forstner, Maria; Hector, Andreas; Griese, Matthias
Summary: Objective: To retrospectively identify CF patients with methicillin resistant Staphylococcus aureus (MRSA) and to assess the long‐term success of an eradication scheme introduced in 2002 for all newly colonized patients. Patients: All microbiological results from all 505 CF patients followed between 2002 and 2012 were analyzed focusing on the detection of MRSA. Methods: Retrospective patient record analysis of MRSA positive CF patients regarding eradication and clinical outcome. Results: We identified 57 patients with MRSA, mean age 15.3 years (range: 0.6–36.9, incidence 0.9%/year). Of these, nine patients were lost to follow‐up; seven chronically colonized patients were excluded from the intervention. Eradication was suggested to all patients, 37/41 gave their consent to the following two‐step approach: (i) dual iv antibiotic treatment over 3 weeks, accompanied by hygienic directives and topical therapy for 5 days followed by a 6‐week period with dual oral antibiotic therapy and inhalation with vancomycin. (ii) Each new MRSA detection was treated with 6 weeks inhalation of vancomycin and topical therapy for 5 days. Long‐term eradication was rated by the microbiological status in the third year after first detection. MRSA was eradicated in 31 of 37 patients (84%) whose clinical course was stable (mean FEV1 one year before MRSA 80.4%, 3 years after MRSA 81.0%). Conclusions: MRSA colonization mandates complex and expensive hygienic measures which are not well accepted by patients. Therefore, MRSA eradication is desirable. Intensive therapy regimens may be successful in patients with CF and might help to maintain a stable clinical course.Pediatr Pulmonol. 2016;51:1010–1019. © 2016 Wiley Periodicals, Inc.